Perbandingan Gesture dan Mimik Dalam Budaya Jerman Indonesia - Kastanya, Melyan Priska; Karuna, Kalvin; Serpara, Henderika (J-EDu: Journal - Erfolgreicher Deutschunterricht, 2025)
Understanding other cultures is essential, not only for those working in the tourism and hospitality sectors but also for anyone who interacts with people from different cultural backgrounds. People often have different perceptions of other cultures, which may lead to negative judgments. These differences in thinking highlight the need for mutual understanding, both internally and externally. Therefore, this study aims to examine intercultural aspects between Germany and Indonesia, focusing on nonverbal communication—particularly gestures and facial expressions. This research seeks to identify the similarities and differences in gestures and facial expressions between German and Indonesian cultures. Nonverbal communication refers to communication conveyed indirectly through body language or signals. It plays an important role in interaction, encompassing body movements and facial expressions. Both German and Indonesian cultures possess a wide variety of gestures and facial expressions with diverse meanings and purposes. Data were collected by observing videos and reviewing references that document various types of gestures and facial expressions. The findings reveal that there are both similarities and differences in nonverbal expressions between German and Indonesian cultures. Based on these findings, it is important to understand and recognize each culture’s nonverbal communication patterns to avoid misunderstandings regarding gestures and facial expressions or their meanings across cultures.